Fertilização do solo com efluente da piscicultura no cultivo de milho crioulo - Souza, Ana Cláudia Medeiros (Universidade Federal Rural do Semi-Árido, 2018)
Considering the low supply of fresh surface water, it is important to develop research and technologies that allow the use of alternative sources of water in agriculture, such as saline water, brackish water and effluents from different activities. In this context, the use of effluent as water and nutritional source is an effective way to control pollution and a viable alternative to increase water availability in arid and semi-arid regions, reducing treatment’s costs and working as a source of nutrients for plants. The aim was to evaluate the use of fish farming effluents in maize. The research was carried between May and July 2016, under field conditions, in a randomized block design, in subdivided plots and 3 replicates. The main treatments consisted of 5 effluent proportions from the activity in the irrigation water (100% control supply water), 75% supply water + 25% effluent, 50% supply water + 50% fish effluent, 25 % water supply + 75% fish effluent and 100% fish effluent), and in the subplots two maize varieties (Ibra and Milho Roxo) were tested. The cultivation of the varieties of Creole, Ibra and Milho Roxo, with fish effluent in irrigation proved viable, being an alternative for treatment and adequate final disposal for this liquid residue, besides being a way to save water resources of good quality and minimize the environmental impact caused by it. The cultivar Ibra presented better results in the vegetative and composition characteristics of the Creole maize’s plant tissue. When applied to the soil, the proportion of 100% of fish effluent causes a reduction in the quality of Creole maize and, consequently, a decrease in the biomass production of this crop and/or high concentrations in the plant tissue
Keywords: Reuso de água; Agricultura familiar; Milho crioulo; Desenvolvimento sustentável; Water reuse; Family farming; Creole corn; Sustainable development; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO